El espíritu del 48. ([San José, Costa Rica], 2002)
Sitio dedicado a preservar los valores e ideales que inspiraron la Revolución de 1948
Keywords: FIGUERES FERRER, JOSÉ -- 1906-1990; COSTA RICA -- HISTORIA -- REVOLUCION, 1948